Influence of Experiental Attitude to Recommendation Intention Through Experiental Satisfaction and Repurchase Intention on Air Asia Airlines Customer at Surabaya - Hartono D., Adrian (Kajian Ilmiah Mahasiswa Manajemen, 2013)
Experiential attitude is defined as the positive or negative behavioral tendencies of the consumers of perceived experiences arising during consumption processes. Experiential satisfaction in this research is the broader concept of satisfaction services, exploration services and influence consumer satisfaction in certain circumstances. Repurchase intention is the willingness of consumers to maintain a relationship of transactions with service providers after the experience of consumption. Intention is the willingness of consumer Recommendation to recommend other people to deal with service providers after the experience of consumption. The research aims to know the influence of experiential attitude and experiential satisfaction of repurchase intention and the intention of recommendation on Air Asia flight service in Surabaya. In this study used is the conclusive research on the study of experimental or causal research. Samplingtaking techniques used are non probability sampling. The type of method used is the purposive sampling. The sample used was 200 consumers Air Asia in Surabaya. Data were collected using a questionnaire. The technique used is the analysis of structural equation modeling with Lisrel program assistance. The results of this analysis indicate that the experiential attitude affect directly to the experiential satisfaction. and an indirect effect of recommendation intention. In addition, the study found that the direct effect of experiential satisfaction repurchase intention and recommendation intention, as well as contributing indirectly to the intention to repurchase intention recommendation as a mediator. Eventually repurchase intention was found to also have influence on the recommendation intention